Labile Dissolved Organic Matter Compound Characteristics Select for Divergence in Marine Bacterial Activity and Transcription - Pontiller, Benjamin; Martínez-García, Sandra; Lundin, Daniel; Pinhassi, Jarone (Frontiers in Microbiology, 2020)
Bacteria play a key role in the planetary carbon cycle partly because they rapidly assimilate labile dissolved organic matter (DOM) in the ocean. However, knowledge of the molecular mechanisms at work when bacterioplankton metabolize distinct components of the DOM pool is still limited. We, therefore, conducted seawater culture enrichment experiments with ecologically relevant DOM, combining both polymer and monomer model compounds for distinct compound classes. This included carbohydrates (polysaccharides vs. monosaccharides), proteins (polypeptides vs. amino acids), and nucleic acids (DNA vs. nucleotides). We noted pronounced changes in bacterial growth, activity, and transcription related to DOM characteristics. Transcriptional responses differed between compound classes, with distinct gene sets (“core genes”) distinguishing carbohydrates, proteins, and nucleic acids. Moreover, we found a strong divergence in functional transcription at the level of particular monomers and polymers (i.e., the condensation state), primarily in the carbohydrates and protein compound classes. These specific responses included a variety of cellular and metabolic processes that were mediated by distinct bacterial taxa, suggesting pronounced functional partitioning of organic matter. Collectively, our findings show that two important facets of DOM, compound class and condensation state, shape bacterial gene expression, and ultimately select for distinct bacterial (functional) groups. This emphasizes the interdependency of marine bacteria and labile carbon compounds for regulating the transformation of DOM in surface waters.